Sentiments of a British-American Woman : Esther DeBerdt Reed and the American Revolution - Ireland, Owen S. (Book collections on Project MUSE., 2017)
"Explores the life and work of political publicist and strategist Esther DeBerdt Reed, who, in a life highly structured by conflict, national identity, religion, and the overall importance of being a wife and mother, gave eloquent expression to the political aspirations of female patriots in Revolutionary America"--Provided by publisher.